Pegylated metal-free and zinc(II) phthalocyanines: synthesis, photophysicochemical properties and in vitro photodynamic activities against head, neck and colon cancer cell lines - Akkoc, Berkay; Samsunlu, Taylan; Isik, Seyma; Ozcesmeci, Mukaddes; Atmaca, Goknur Yasa; Erdogmus, Ali; Serhatli, Muge; Hamuryudan, Esin (ROYAL SOC CHEMISTRY, 2022)
In this study, a series of peripherally and non-peripherally tetra-substituted metal-free and zinc(s) phthalocyanines were successfully prepared in good yields by cyclotetramerization of the phthalonitrile derivative bearing a tetraethylene glycol methyl ether group at 3- and 4- positions. All newly synthesized compounds were characterized using spectroscopic methods, such as FT-IR, NMR, mass and UV-Vis spectroscopy. To determine the therapeutic potential of the synthesized phthalocyanines, the effects of the substitution pattern (peripheral and non-peripheral) and central metal atom on the photophysicochemical properties were investigated. When comparing their singlet oxygen generation capabilities (Phi(Delta)), metallo-phthalocyanine derivatives with zinc (0.73 for 1b and 0.70 for 2b) showed higher singlet oxygen yield than metal-free derivatives (0.21 for 1a and 0.12 for 2a) in DMSO. The photodynamic therapy activities of the water-soluble phthalocyanines were tested via in vitro studies using the A253, FaDu (head and neck cancer cell lines), and HT29 (colon cancer) cell lines. The strongest photodynamic activity was found in 1b and 2b molecules with a metal core among the four molecules studied. The results suggested that the non-peripherally tetra-substituted 1b molecule was regarded as a suitable photodynamic therapy agent due to its light cytotoxicity and secondary impact induced by ROS production.
Keywords: AMPHIPHILIC PHTHALOCYANINES; THERAPY; PHOTOSENSITIZERS; SUBSTITUENTS; CONJUGATE; Chemistry